Properties of Doped GaSb Whiskers at Low Temperatures - Khytruk, Igor (Nanoscale Res Lett, 2017)
Temperature dependencies of GaSb whiskers’ resistance doped with Te to concentration of 1.7 × 10(18) cm(−3) were measured in temperature range 1.5–300 K. At 4.2 K temperature, a sharp drop in the whisker resistance was found. The observed effect is likely connected with the contribution of two processes such as the electron localization in the whiskers and transition in superconducting state at temperature below 4.2 K. The whisker magnetoconductance is considered in the framework of weak antilocalization (WAL) model and connected with subsurface layers of the whiskers. The Shubnikov-de Haas (SdH) oscillatory effect is observed in high-quality n-type GaSb whiskers with tellurium doping concentration near the metal-insulator transition (MIT) for both longitudinal and transverse magnetoresistance.